A Comprehensive Pharmacognostical and Pharmacological Overview of Mimosa Pudica Linn - Bharati, Sarswati; Tiwari, Sampurnanand (Journal of Neonatal Surgery, 2025)
Mimosa pudica Linn., commonly known as the “touch-me-not” plant, is a perennial creeping herb belonging to the family Fabaceae, noted for its rapid seismonastic movement upon tactile stimulation. It holds a significant place in traditional medical systems such as Ayurveda, Siddha, and Unani, where it is used for a wide range of ailments. The plant is widely distributed across tropical and subtropical regions. Pharmacognostically, it is distinguished by its bipinnate sensitive leaves, pink globose inflorescences, and prickly stems. Microscopic evaluation reveals diagnostic features such as paracytic stomata, unicellular trichomes, and prismatic calcium oxalate crystals. Phytochemical analyses have identified diverse bioactive constituents including alkaloids, flavonoids, tannins, glycosides, saponins, terpenoids, and phenolic compounds, which contribute to its pharmacological versatility.Modern pharmacological studies substantiate its wide therapeutic profile, demonstrating antimicrobial, anti-inflammatory, antidiabetic, antivenom, wound-healing, hepatoprotective, antioxidant, antiulcer, and antidepressant activities. Many of these effects correlate with its traditional uses, such as in treating wounds, urinary disorders, and inflammatory conditions. Furthermore, emerging experimental data suggest potential roles in neuroprotection and cancer chemoprevention, although clinical evidence remains limited.This review aims to integrate classical knowledge with contemporary pharmacological findings, providing a consolidated understanding of M. pudica. Special emphasis is placed on its botanical description, pharmacognostic parameters, phytochemical constituents, and experimentally validated pharmacological activities. Existing research gaps, particularly in the areas of compound isolation, clinical trials, and formulation standardization, are highlighted to guide future drug development